Pengawasan Persediaan Bahan Baku Garam Kasar pada UD. Petasikan Pesanggaran, Denpasar Selatan - SUCAHYO, IRFANSYAH; YUDHARI, I DEWA AYU SRI; YUSUF, RIA PUSPA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.5, Desember 2015, 2016)
ABSTRACT Inventory Control Of Raw Material Of Salt Coarse In UD. Petasikan Pesanggaran, South Denpasar Raw material is one the most important factors in the production process, therefore, the inventory of the raw material demands to be controlled, in order not only to avoid surplus and/or deficiency of the raw material but also to make the total inventory cost more efficient. The research is conducted in UD. Petasikan Pesanggaran, South Denpasar with a view to know the production process of fine salt in the company, to analyze the inventory of the raw material and the total of efficient inventory cost. The research makes use of descriptive quantitative method. The result of the research shows that: 1) the company should have gained the total economic order quantity (EOQ) as much as 101.04 tons per one-time booking; 2) the company should have kept at least 7.04 tons of the total safety stock; 3) the company should have done reordering (reorder point) when the total basic commodity reached 14.08 tons, and 4) the company should have gained the total of maximum inventory as much as 108.08 tons. Based on the analysis of the efficient supply of raw material, the researcher knows that the total inventory costs need to be incurred by the company during the period amounted               Rp. 6,375,460.46 resulting in saving of Rp. 2,332,739.54 or as much as 26,79 % of production cost. In  conclusion, the use of economic order quantity (EOQ) method continuously is considerably very beneficial for the company because it can determine the total purchase of raw material economically and reduce the excessive inventory cost. Keywords: salt, inventory control, economic order quantity